Spatiotemporal distribution and risk factors for patient and diagnostic delays among groups with tuberculous pleurisy: an analysis of 5-year surveillance data in eastern China - Li, Yang; Luo, Dan; Zheng, Yi; Liu, Kui; Chen, Songhua; Zhang, Yu; Wang, Wei; Wu, Qian; Ling, Yuxiao; Zhou, Yiqing; Chen, Bin; Jiang, Jianmin (Frontiers in Public Health, 2024)
Objective: To understand and analyze the factors relating to patient and diagnostic delays among groups with tuberculous pleurisy, and its spatiotemporal distribution in Zhejiang Province.Methods: Data of all TP patients were collected from the existing tuberculosis information management system. A time interval of > 2 weeks between first symptom onset and visit to the designated hospital was considered a patient delay, and a time interval of > 2 weeks between the first visit and a confirmed TP diagnosis was considered a diagnostic delay. Univariate and multivariate logistic regression analyses were used to explore factors influencing patient and diagnostic delays in patients with TP. Spatial autocorrelation and spatiotemporal scan analyses were used to identify hot spots and risk clusters, respectively.Results: In total, 10,044 patients with TP were included. The median time and interquartile range for patients seeking medical care and diagnosis were 15 (7-30) and 1 (0-8) days, respectively. The results showed that people aged > 65 years, retirees, and residents of Jinhua, Lishui, and Quzhou were positively correlated with patient delay, whereas retreatment patients, houseworkers, unemployed people, and residents of Zhoushan or Ningbo were positively correlated with diagnostic delay. Additionally, high-risk clusters of patient delays were observed in the midwestern Zhejiang Province.The most likely clusters of TP diagnostic delays were found in southeast Zhejiang Province.In summary, patient delay of TP in Zhejiang province was shorter than for pulmonary tuberculosis in China, while the diagnostic delay had no difference. Age, city, occupation, and treatment history were related to both patient and diagnostic delays in TP. Interventions in central and western regions of Zhejiang Province should be initiated to improve the early detection of TP. Additionally, the allocation of health resources and accessibility of health services should be improved in the central and eastern regions of Zhejiang Province.